Still here : embracing aging, changing, and dying - Ram Dass (Riverhead Books, 2001)
"More than thirty years ago, an entire generation sought a new way of life, looking for fulfillment and meaning in a way no one had before. Leaving his teaching job at Harvard, Ram Dass embodied the role of spiritual seeker, showing others how to find peace within themselves in one of the greatest spiritual classics of the twentieth century, Be Here Now. As many of that generation enter the autumn of their years, the big questions of peace and of purpose have returned demanding answers. And once again, Ram Dass blazes a new trail, inviting all to join him on the next stage of the journey."--P. [4] of cover.